Evaluating the delivery, impact, costs and benefits of an active lives programme for older people living in the community. Issue 2 (19th August 2016) - Gandy, Rob; Bell, Amelia; McClelland, Bob; Roe, Brenda
Abstract : Aim: Age UK Lancashire received Big Lottery funding to deliver an active lives programme from January 2012 to December 2014 to the population of West Lancashire aged over 50 years. The overall aims of the associated evaluation were to measure older people's experiences of participating in the programme, identify the impacts on their health and well-being and their suggestions for services development, and establish the costs and benefits of the programme. Background: The World Health Organisation recommends older people should be able to achieve physical, social and mental well-being throughout their lives, and that international, national and local policies should be developed to support older adults, promote their independence and well-being, and encourage physical exercise. Consequently, the West Lancashire programme was to establish preventative community support for older people to assist in improving their well-being and physical and mental health, particularly those isolated due to age-related illness or disability. It was to provide interventions not available from local social care providers. Methods: A mixed methods approach was adopted, with the qualitative evaluation utilising focus groups to establish people's experiences, identify impacts on their health and well-being, and suggestions for services development. This paper describes the quantitative evaluation, which involved three surveys and a costs analysis. The surveys were scheduled to give timely feedback to management about programme delivery and content, and overall benefits of participation. Findings: The active lives programme and groups offered a wide range of flexible and local activities that provided benefits for older people in terms of health and well-being, social well-being and quality of life, and reducing social isolation. There was interconnectivity between these benefits. The programme was delivered in an affordable and flexible manner. Such programmes should be made more widely available.